Rotavirus vaccine dose-two dropout and its associated factors among children who received rotavirus vaccine dose-one in Sub-Saharan African countries: A multilevel analysis of the recent demographic and health survey - Belayneh Shetie Workneh; Enyew Getaneh Mekonen; Alebachew Ferede Zegeye; Almaz Tefera Gonete; Tewodros Getaneh Alemu; Tadesse Tarik Tamir; Berhan Tekeba; Mulugeta Wassie; Alemneh Tadesse Kassie; Mohammed Seid Ali (Human Vaccines & Immunotherapeutics)
Rotavirus is the most common cause of diarrhea in children worldwide. In 2016, rotavirus infection resulted in 258 173 300 episodes of diarrhea and 128 500 child deaths in the globe. The study aimed to assess the magnitude of Rotavirus vaccine dose-two dropout and associated factors among children who received rotavirus vaccine dose-one in sub-Saharan African countries. The appended and most recent demographic and health survey (DHS) dataset of 17 sub-Saharan African countries was used for data analysis. A total of 73,396 weighted samples were used. Factors associated with the outcome variable were considered significant if their p-values were ≤ .05 in the multilevel mixed-effect logistic regression model. The overall Rotavirus vaccine dose-two dropouts was 10.77% (95% CI 10.55%, 11.00%), which ranged from 2.77% in Rwanda to 37.67% in Uganda. Being younger, late birth order, having difficulty accessing health facilities, having no media exposure, having no work, having home delivery, having no antenatal follow-up, and having no postnatal checkup were factors significantly associated with the outcome variable. The overall Rotavirus vaccine dose-two dropout was higher in sub-Saharan African countries which implies that vaccine dropout is still a great issue in the region. Special attention should be given to those mothers who are young, who have no work, who give birth at home, who experienced difficulty in accessing health facilities, and late birth orders. Furthermore, targeted interventions should be considered for improving access and utilization of media, antenatal care, and postnatal care services.